IMPROVING THE QUALITY OF EDUCATIONAL HUMAN RESOURCES TO ACHIEVE INDONESIA'S VISION 2045 - Elmi, Farida; Librianty, Nany (Jurnal Apresiasi Ekonomi, 2023)
This research was conducted with a descriptive qualitative type, in accordance with the readiness in the education industry to obtain outcomes regarding the quality of the Indonesian nation's human resources in facing the golden year 2045 as seen from the PISA (Program for International Student Assessment) scores, international achievements in the fields of literacy, mathematics and science in high school students / grades 9-10 at the age of 15 in the province of Bangka-Belitung. The results from observations enriched by SINTA accredited national journals and reputable international journals are strengthened by several references and secondary data, with the era this pandemic, has forced us to innovate and be competent and professional in mastering digital technology, so we need to work hard and be extra focused to improve ourselves from the policies contained in the law, the education system and the quality of teachers, so that students/students become habitual and culture in the PISA score measurement indicator which is the main standard so that Indonesia can align with the PISA standard determined by the OECD (The Organization for Economic Cooperation and Development) which is followed by developed countries and developing countries to produce high-quality human resources. international/global. When the PISA ranking in the province of Bangka-Belitung continues to improve and advance in the long term, it becomes an obligation for all provinces in Indonesia, so that by itself Indonesia will become the most prosperous and prosperous country.